Corruption in the Christian Nation "Does the Christian Faith Influence the Level of Corruption Within a Society?" - Kraus, František; Houdek, Petr, 1981-; Svoboda, Miroslav; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2013)
What are the determinants of corruption? This thesis builds upon contemporary approaches to assessing the level of corruption in different countries using purely economic determinants such as the aggregate income, level of education, openness to trade or taxation. This method is further enhanced by involving variables mapping the religiosity of the surveyed states as institutional determinants. Faith works as an agent that reduces selfish behavior and stresses moral values, thus it should prove to reduce corruption. The dataset involves data of 30 countries of the Organization for Economic Cooperation and Development (OECD) in the years 1999-2010. Two independent OLS models are set up using corruption perception indicators as endogenous variables; one with purely economic determinants, and the other with added religious determinants of corruption. Expansion of the model gives out a more robust set of results with greater determination. The results show that increasing number of Protestants in a society correlates with lower levels of corruption. The effect of the government spending on education has been considerably reduced after involving the religious variables. However, corruption does not seem to be influenced by the percentage of Christians in total population.
Vedoucí práce: Petr Houdek
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses